Immune Responses of Goats to Corynebacterium pseudotuberculosis and its Mycolic Acids (MAs) Extract - Naji Odhah, Mohammed; Abdullah Jesse, Faez Firdaus; Paul, Bura Thlama; Garba, Bashiru; Mahmood, Zaid; Lim, Eric Teik Chung; Mohd Lila, Mohd Azmi (Nexus Academic Publishers, 2023)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis in small ruminants and is of considerable economic importance in many countries worldwide. The control of the disease in animals depends on the control of the disease in infected animals. Nevertheless, few countries where the disease was previously endemic have successfully eradicated the pathogen. This investigation was undertaken to determine the antibody titre (IgM and IgG) in does challenged with C. pseudotuberculosis and its Mycolic acids (MAs) immunogen extract. About 12 healthy crossbred female Boer goats were assigned into three groups (A, B and C), each comprising of 4 goats. Group A (Negative control group) was inoculated intradermally with 2 ml of sterile phosphate-buffered saline (PBS-pH 7); Group B (Mycolic acid group) was inoculated intradermally with 2 ml of immunogenic Mycolic acid extract (1g /ml); while group C (Positive control group) was inoculated intradermally with 2 ml of 109 colony-forming unit of live C. pseudotuberculosis. All the animals were observed for 90 days post-inoculation. Blood samples were collected via the jugular vein from all the groups before the inoculation and once weekly after the challenge until the end of the research period. The result of the study showed that the Immunoglobulin M (IgM) concentration in goats inoculated with C. pseudotuberculosis significantly (p